2017
DOI: 10.1111/aji.12790
|View full text |Cite
|
Sign up to set email alerts
|

A distinct mechanism of senescence activation in amnion epithelial cells by infection, inflammation, and oxidative stress

Abstract: TNF-α caused OS-mediated p38MAPK induction, senescence, and IL-6 increase from AECs. LPS also induced senescence and IL-6 increase. Inflammatory and infectious factors may cause premature fetal cell senescence contributing to preterm birth pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…Examination of pPROM membranes indicated signs of premature senescence activation (or accelerated aging of membranes) prior to term to oxidative stress-inducing risk factors [34,35]. In vitro, we have shown that infection, inflammation, and environmental and behavioral risk factors can accelerate cell senescence in fetal membranes [20,21,24,36]. Thus, senescence-associated cellular level changes in fetal membranes contribute to an inflammatory process by not only weakening the membranes but disabling their functional capabilities.…”
Section: Senescence Of Fetal Membranesmentioning
confidence: 85%
See 1 more Smart Citation
“…Examination of pPROM membranes indicated signs of premature senescence activation (or accelerated aging of membranes) prior to term to oxidative stress-inducing risk factors [34,35]. In vitro, we have shown that infection, inflammation, and environmental and behavioral risk factors can accelerate cell senescence in fetal membranes [20,21,24,36]. Thus, senescence-associated cellular level changes in fetal membranes contribute to an inflammatory process by not only weakening the membranes but disabling their functional capabilities.…”
Section: Senescence Of Fetal Membranesmentioning
confidence: 85%
“…Generation of balanced inflammation maintains membrane integrity through controlled remodeling whereas persistence of inflammation either due to physiologic (term) or pathologic (preterm) can be considered as fetal/host inflammatory response causing membrane weakening, rupture [16]. The inflammation observed in fetal membranes is 'sterile inflammation' [20] during normal pregnancy that are physiologic host response whereas the contributors of inflammation in preterm membranes are often 'infectious' [21] in response to microbial invasion of the amniotic cavity. Sterile inflammation is also reported in the absence of infection in pregnancy pathologies in response to various non-infectious risk factors [20].…”
Section: Senescence Of Fetal Membranesmentioning
confidence: 99%
“…For the transmission electron microscopy (TEM) analysis, sEV samples were fixed in 3% (w/v) glutaraldehyde and analysed as previously described [40,41]. Briefly, 5 µL of each sample was adsorbed on Formvar carbon-coated and glow-discharged electron microscopy grids.…”
Section: Salivary Sevs Characterisationmentioning
confidence: 99%
“…Fetal membranes collected on different gestational days were lysed with RIPA lysis buffer (50 mmol/L Tris pH 8.0, 150 mmol/L NaCl, 1% Triton X‐100, and 1.0 mmol/L EDTA pH 8.0, 0.1% SDS) supplemented with protease and phosphatase inhibitor cocktail and phenylmethylsulfonyl fluoride as described previously by our laboratory . A Pierce BCA Protein Assay Kit (Thermo Scientific) was utilized to determine protein concentration of samples, and 45 µg of tissue lysate was used for loading the gels for Western blotting, which was performed as previously described by our laboratory . Briefly, samples were run on gradient (4%‐15%) SDS‐PAGE Mini‐PROTEAN TGX pre‐cast gels (Bio‐Rad) and transferred to the membrane using a Bio‐Rad gel transfer device (Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%